Irish Protestant identities - Busteed, Mervyn A.; Neal, Frank; Tonge, Jonathan (Manchester Univ. Press, 2008)
This multi-disciplinary portrayal and analysis of the Protestant tradition in Ireland examines Protestant contributions to literature, culture, religion and politics. It also assesses Protestant authors, churches, Orange Order, Unionist Parties and Ulster loyalism